2021
DOI: 10.1016/j.bpobgyn.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of infection to patients and staff during gynaecological outpatient and ambulatory appointments

Abstract: This chapter explores ways of reducing the risk of SARS-CoV-2 transmission to women and staff within gynaecology outpatient clinics. The likely routes of transmission are discussed, namely via droplets, aerosols and fomites. Using the 'hierarchy of control' categories, elimination, substitution, engineering, administration and personal protective equipment (PPE), practical strategies for modifying virus exposure are presented. The management of specific clinical conditions are reviewed based upon advice prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Substantial changes in the delivery of healthcare services have been made in several other countries as well, in an effort to minimize transmission risks [61]. Such changes include minimizing face-to-face care, physical-distancing restrictions, reducing care, limiting women's escorts during appointments and childbirth, and restricting visitors to maternity wards [62,63]. Additional studies have reported that perinatal women experience high levels of concern about birth expectations, as well as report feelings of fear and loneliness [64], while postpartum women are concerned about breastfeeding and infant weight gain due to lack of face-to-face contact with health professionals [65].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial changes in the delivery of healthcare services have been made in several other countries as well, in an effort to minimize transmission risks [61]. Such changes include minimizing face-to-face care, physical-distancing restrictions, reducing care, limiting women's escorts during appointments and childbirth, and restricting visitors to maternity wards [62,63]. Additional studies have reported that perinatal women experience high levels of concern about birth expectations, as well as report feelings of fear and loneliness [64], while postpartum women are concerned about breastfeeding and infant weight gain due to lack of face-to-face contact with health professionals [65].…”
Section: Discussionmentioning
confidence: 99%